The depiction of Jews in Middle English crucifixion literature - Smurthwaite, Cynthia Laurie (University of Ottawa (Canada), 2003)
This thesis studies the relationship between the treatment of Jewish characters by Christian authors in Middle English Crucifixion literature and the treatment of Jews in medieval Europe by members of surrounding Christian majority cultures. The common medieval Christian belief that all Jews, of all periods and places, were responsible for Jesus' death led to the related beliefs that there was a singular Jewish character; that it was racially determined; and that it was evil. The exaggerated role Jews play in Middle English versions of the Crucifixion, and the authors' various derogatory references to Jews in general, were designed in part to reconcile medieval Christians to the uncharitable treatment endured by Jews in their midst. Christian writers often attributed to Jews certain negative characteristics that determined their alienation both from God and from the rest of humanity. These characteristics were exemplified by unsuccessful figures from Hebrew scripture: sons of holy men who, far from fulfilling the promise of their fathers, failed to earn God's favour, and thus were excluded from election. Cain, for example, became a model of violence; Ishmael became a model of exile from the Holy Land; and Esau became a model of love of the world over the spirit. This thesis organizes its study of Christian portrayals of gospel and post-gospel Jews according to the precedents set by these three early models of a common Christian stereotype of Jews. Because these characters' failure is linked to the success of their younger siblings, this thesis also places their putative legacy to later Jews in the context of ultimogeniture, according to which, as many medieval Christians believed, God recalled his promise to the Jews and granted it instead to the new faith of Christianity. The texts studied herein portray Jews as members of a wayward faith, deprived of their ancient status on account of the Crucifixion.
Keywords: Literature, English.